Full moon party - Young, Jessica (Jessica E.); Vanderbemden, Marie (New York, NY : Scholastic Inc., 2021)
Best friends Ruby, Iris, and Pip, together with their teacher, Miss Goldwing, set out on a field trip to the Full Moon Fest, following the magic path that appears when the full moon shines on Moon Lake--and once there they find plenty of games, snacks, and dancing.
1.8.
K-3.
400L
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Festivals -- Juvenile fiction; Best friends -- Juvenile fiction; Fairies -- Fiction; Magic -- Fiction; Festivals -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Fantasy; Fantasy fiction